2022
DOI: 10.2196/30108
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Egyptian Web-Based Health Information Seekers Toward Health Information Provided Through the Internet: Qualitative Study

Abstract: Background The internet has become an established source of health information for many Egyptian internet users. Understanding users’ attitudes toward the benefits and limitations of web-based health information will explain the influence of this information on users’ health-related behavior and decisions. Objective This qualitative study aims to understand the attitude of Egyptian internet users toward internet health information and to explore the imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The study of Ghweeba et al (2022) aims to understand the attitude of Egyptian internet users toward health websites and to explore the impact of obtained health information on users' behavior. The authors used qualitative study and semi structured interviews were conducted with a total of 49 participants.…”
Section: Arabic Health Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Ghweeba et al (2022) aims to understand the attitude of Egyptian internet users toward health websites and to explore the impact of obtained health information on users' behavior. The authors used qualitative study and semi structured interviews were conducted with a total of 49 participants.…”
Section: Arabic Health Contentmentioning
confidence: 99%
“…The results showed that the internet has become an important source of health information and is the central theme that has emerged across the thematic analysis. The attitude toward the use of health websites was classified into three main themes: feelings toward web-based health information, motivators to seek health websites, and behavioral changes using health information (Ghweeba et al, 2022).…”
Section: Arabic Health Contentmentioning
confidence: 99%